Optimizing the Medicine Procurement Process - Mani, Vijaya; Haridasan, Vani (International Journal of Engineering and Technology, 2018)
Purpose: The major focus of the research was to improve and suggest cost effective medicines to the hospital by identifying, documenting and analyzing the various issues in drug utilization pattern. It also aimed to optimize the rational use of medicines in the selected Â Hospital in Tamil Nadu.Approach: The Inventory Management techniques like ABC and VEN analysis were done on 414 medicines by utilizing the annual consumption and expenditure data extracted from the Hospital records.Results: The research could identify the medicines (A category- ABC) which require stringent management managerial control and also identified the vital drugs (VEN)which should be made available at all times in the hospital in order to improve the hospital efficiency.Â Â
Keywords: Consumption; Utilization; Inventory Management; Categorization; Optimization.